(untitled) (Journal of Hama University, 2026)
Crises are important and influential events in organizations. They have become an integral part of today’s environment and pose a concern for both organizational leaders and officials. These crises are difficult to control, due to the sharp and sudden changes in the external environment, on the one hand, and the weakness of responsible departments in adopting an appropriate management model that enables the organization to quickly and effectively confront crises, on the other. Therefore, the current study aims to evaluate the practices of heads of nursing departments during a crisis in the hospital. The sample included 54 heads of nursing departments working at the National Hospital in Tartous. Data was collected using a tool developed by the researcher. The results showed that nursing department heads’ practices were weak during the crisis. This was evident in their lack of prior planning for crisis management, their lack of crisis response training, and their inability to anticipate potential difficulties that the hospital might face. Furthermore, more than half of the sample had never anticipated or participated in anticipating difficulties and crises before they occurred. Additionally, nearly half of the sample had not undergone crisis management training. There was a weakness in nursing department heads’ practices in developing plans to address the coronavirus crisis in the hospital, as well as their inability to handle the workload during the coronavirus crisis.